The solution for the given equations
and
are (x, y) respectively (5, 3).
Explanation:
The given is,
.................................................(1)
........................................................(2)
Step:1
By using the elimination method for the above equations are,
Multiply the equation (2) by 2 ( Eqn(2) × 2)
.............................................(3)
Step:2
Subtract the Equation (1) and (3),
![2x-5y=-5](https://img.qammunity.org/2021/formulas/mathematics/middle-school/wucm00xb6d1w3ipf99jqkfm6f5lnwebl7l.png)
![2x+2y=16](https://img.qammunity.org/2021/formulas/mathematics/middle-school/ht0aabnoyztwy8oxuml1chok9dlkipk9yq.png)
( - )
(
-
) + (
-
) = (
-
)
=
![-21](https://img.qammunity.org/2021/formulas/mathematics/middle-school/4sleo2nfcdy6z1fqgndb2xwfcy1m1y7vq7.png)
= 3
Step:3
Substitute the value of y in Eqn (2),
............................(2)
![x+3=8](https://img.qammunity.org/2021/formulas/mathematics/middle-school/2kdadmcwwq1knzarkr5hg30y8yv3752zbk.png)
![x=8-3](https://img.qammunity.org/2021/formulas/mathematics/middle-school/i3fqwamslas1d6v7ql9lmjue3z2h0jb38b.png)
![x=5](https://img.qammunity.org/2021/formulas/mathematics/middle-school/r130cmidu5qpu4isx9n84rpneq2ec7gp1u.png)
Step:4
Check for solution,
Substitute the x and y values in Eqn (1),
........................(1)
(2 × 5) - (5 × 3) = -5
10 - 15 = -5
-5 = -5
Result:
The solution for the equations
and
are (x, y) respectively (5, 3).